A Review on Fullerene Derivatives with Reduced Electron Affinity as Acceptor Materials for Organic Solar Cells - Alexander V. Mumyatov; Pavel A. Troshin (Energies, 2023)
Organic solar cells (OSCs) represent a promising emerging photovoltaic technology offering such benefits as light weight, mechanical flexibility, semitransparency, environmental friendliness and aesthetic design of solar panels. Furthermore, organic solar cells can be produced using scalable and high-throughput solution-based printing and coating technologies, which are expected to lead to very low product costs. Fullerene derivatives have been used as acceptor materials in virtually all efficient organic solar cells for more than two decades, following the demonstration of the first proof-of-concept devices in the middle of 1990s. Still, the power conversion efficiencies of fullerene-based organic solar cells became stuck at around 12% due to the suboptimal optoelectronic properties of conventional fullerene acceptors. Therefore, the latest efficiency records (>18%) for organic solar cells were set using different types of non-fullerene acceptor (NFA) materials with tailorable properties. However, NFA materials appeared to be very sensitive to light, thus impairing the operational stability of OSCs. On the contrary, there is growing evidence that rationally designed fullerene-based acceptors enhance the photostability of conjugated polymers and also NFAs, when used in ternary blends. Hence, a renaissance of fullerene-based materials is currently expected in the context of their use in multicomponent organic solar cells (e.g., as stabilizers) and also lead halide perovskite solar cells, where they play an important role of electron transport materials. The success in both of these applications requires the tunability of optoelectronic characteristics of fullerene derivatives. In particular, electron affinity of the fullerene cage has to be reduced in many cases to match the energy levels of other absorber material(s). Herein, we present a systematic review of different strategies implemented to reduce the acceptor strength of the fullerene derivatives and the results of their performance evaluation in OSCs with model conjugated polymers. Particular attention is paid to correlations between the chemical structure of organic addends and their influence on the electronic properties of the fullerene core. We believe this review would be valuable to researchers working on the rational design of new fullerene-based materials with tailored properties for photovoltaic and other electronic applications.